Efek Puasa 12 Jam dari Fajar Hingga Terbenam Matahari Terhadap Sistem Imunitas pada Manusia - Armanto Makmun; Fahirany Noor (Indonesian Journal of Health, 2021)
Abstract: Fasting is to refrain from food for a certain period of time voluntarily. The average fasting period is 12 hours. The effect of fasting on the regulation of the immune system is still difficult to understand. However, changes in the immune system, such as modulation of the body's response to various infections, stress, and other dangerous events, are very interesting during fasting. Periodic fasting reprograms T-cell populations, suppressing autoimmunity and enhancing immunity. Purpose: This study aims to Article Review by looking at the topic of fasting especially towards immunity by using research with quantitative meta-analysis methods based on research that has been done before. Methods: This study uses the article review method. The data source of this research comes from the literature obtained through the internet in the form of research results from international journals in 2011-2020. Results: The results of this study from a total of 51 journals, which the authors have reviewed, the conclusion is the effect of fasting on the immune system is very diverse, can be seen in terms of immunomodulators / markers of inflammation, exercise, metabolism, metabolic diseases such as obesity, diabetes mellitus and infectious diseases, like TB and COVID-19. Therefore, the authors hope that with this Article review can add information to the public about the effects of fasting on the body's immune system. The conclusion of this study based on the results of the study found that the many effects of fasting are very beneficial for improving the body's immune system.